Technology Integration in Physical Education: Impact and Implications for Students and Teachers - Hasmyati (Journal Physical Health Recreation (JPHR), 2025)
The digital transformation in physical education has significantly reshaped pedagogical approaches and learning outcomes. This study aims to review and analyze various forms of technology integration in physical education and their impact on students’ motivation, performance, and teachers’ professionalism. A descriptive literature analysis was conducted using reputable scientific databases covering studies from 2019 to 2025. The findings reveal that digital technologies such as wearable devices, virtual reality (VR), exergaming, fitness applications, and artificial intelligence (AI) systems significantly enhance students’ participation and motivation while enabling teachers to conduct data-driven evaluations. Furthermore, technology fosters inclusive and collaborative learning by positioning students at the center of the learning process. However, challenges such as teachers’ digital literacy, infrastructural disparities, and ethical issues related to data privacy remain critical obstacles. Therefore, the success of technology integration in physical education depends on coordinated efforts among educators, institutions, and policymakers to establish an adaptive, effective, and sustainable learning environment.